Prophylactic Topical Antibiotics in Fracture Repair and Spinal Fusion. (14th October 2021) - Kim, Eric K.; Donnelley, Claire A.; Tiee, Madeline; Roberts, Heather J.; Von Kaeppler, Ericka; Shearer, David; Morshed, Saam
Abstract : Introduction . The objective of this systematic review with meta-analysis is to determine whether prophylactic local antibiotics prevent surgical site infections (SSIs) in instrumented spinal fusions and traumatic fracture repair. A secondary objective is to investigate the effect of vancomycin, a common local antibiotic of choice, on the microbiology of SSIs. Methods . An electronic search of PubMed, EMBASE, and Web of Science databases and major orthopedic surgery conferences was conducted to identify studies that (1) were instrumented spinal fusions or fracture repair and (2) had a treatment group that received prophylactic local antibiotics. Both randomized controlled trials (RCTs) and comparative observational studies were included. Meta-analysis was performed separately for randomized and nonrandomized studies with subgroup analysis by study design and antibiotic. Results . Our review includes 44 articles (30 instrumented spinal fusions and 14 fracture repairs). Intrawound antibiotics significantly decreased the risk of developing SSIs in RCTs of fracture repair (RR 0.61, 95% CI: 0.40–0.93, I 2 = 32.5%) but not RCTs of instrumented spinal fusion. Among observational studies, topical antibiotics significantly reduced the risk of SSIs in instrumented spinal fusions (OR 0.34, 95% CI: 0.27–0.43, I 2 = 52.4%) and in fracture repair (OR 0.49, 95% CI: 0.37–0.65, I 2 = 43.8%). Vancomycin powder decreased the risk of Gram-positive SSIs (OR 0.37, 95% CI: 0.27–0.51, I 2 = 0.0%) and had no effect on Gram-negative SSIs (OR 0.95, 95% CI: 0.62–1.44, I 2 = 0.0%). Conclusions . Prophylactic intrawound antibiotic administration decreases the risk of SSIs in fracture surgical fixation in randomized studies. Therapeutic efficacy in instrumented spinal fusion was seen in only nonrandomized studies. Vancomycin appears to be an effective agent against Gram-positive pathogens. There is no evidence that local vancomycin powder is associated with an increased risk for Gram-negative infection.